Motivação e imaginação no contexto da prática pedagógica e na aprendizagem em química - SANTOS, Priscilany Cavalcante dos (Universidade Federal do Pará, 2023)
The objective of this research is to understand how comprehensive and/or creative chemistry learning is subjectively configured, in the context of investigative practices. The construction of the research theoretical model was based on the principles of Qualitative Epistemology, proposed by González Rey (2005). Such principles relate to knowledge production processes, highlighting the constructive-interpretive character, the interactive character (dialogue) and the singularity. For the construction of the information, instruments such as informal conversations, interviews, videos and images of school actions, written records and the technique of completing sentences were used, based on the hypotheses elaborated in the course of the research. Max's case study and the analysis of the pedagogical practice made it possible to elaborate principles with the intention of contributing to the students' learning. Such principles include curiosity as a guiding principle to encourage imagination, investigative practice as a promoter of imagination and the creation of a pedagogical strategy in teaching and learning in chemistry. In addition, the construction of a pedagogical practice that favors learning includes spaces for dialogue, partnership relationships and knowledge production that allow understanding the student's motivations in the context of learning as a subjective production.